2013
DOI: 10.1128/ec.00278-12
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stress Induces a Conserved Cell Wall Stress Response in the Pathogenic Fungus Candida albicans

Abstract: cThe human fungal pathogen Candida albicans can grow at temperatures of up to 45°C. Here, we show that at 42°C substantially less biomass was formed than at 37°C. The cells also became more sensitive to wall-perturbing compounds, and the wall chitin levels increased, changes that are indicative of wall stress. Quantitative mass spectrometry of the wall proteome using 15 N metabolically labeled wall proteins as internal standards revealed that at 42°C the levels of the ␤-glucan transglycosylases Phr1 and Phr2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 85 publications
(101 reference statements)
5
95
0
3
Order By: Relevance
“…Many of these proteins are also increased in the cell wall of C. albicans cells exposed to Congo red, Calcofluor white (16), or heat stress (17). Interestingly, exposure to fluconazole alters the cell wall proteome similarly to Congo red (16), indicating that plasma membrane stress may cause a cell wall stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these proteins are also increased in the cell wall of C. albicans cells exposed to Congo red, Calcofluor white (16), or heat stress (17). Interestingly, exposure to fluconazole alters the cell wall proteome similarly to Congo red (16), indicating that plasma membrane stress may cause a cell wall stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation for MS analysis was performed as outlined previously (16,17) After treatment of 4 mg of freeze-dried cell wall pellet with 2 g Trypsin Gold (Promega) for 18 h, the resulting peptide mix was desalted using a C 18 tip column (Varian). Next, 250 ng of the desalted peptides in 10 l 0.1% trifluoroacetic acid (TFA) was injected into an Ultimate 2000 nano-high-performance liquid chromatography (nano-HPLC) system (LC Packings) equipped with a PepMap100 C 18 reversed-phase column (75-m inner diameter, 25-cm length; Dionex).…”
Section: Methodsmentioning
confidence: 99%
“…The wall proteome of C. albicans has been extensively studied both qualitatively and quantitatively (39,43). It shows an amazing adaptability that helps the cell to adequately respond to changes in, for example, pH, temperature, hypoxic conditions, carbon source, and iron availability and to plasma membrane and wall stress (43)(44)(45)(46)(47)(48)(49). The wall proteome also reflects morphotype and contains yeast-and hypha-specific wall proteins (50).…”
Section: Quantitative Analysis Of the Cell Walls Of S Cerevisiae Andmentioning
confidence: 99%
“…Most prior A C C E P T E D M A N U S C R I P T by thicker cell walls, which can increase the stress resistance of the cells by regulating their architecture and biophysical properties [5,6]. For example, Gram-positive bacteria have applications in high temperature and extreme pH environments [7][8][9][10]; whereas, studies into the EET mechanism that operates with such microorganisms have rarely reported in detail [11].…”
Section: Introductionmentioning
confidence: 99%